A New Monotypic Genus from the American Southwest to accommodate “Semiothisa” kuschea (Geometridae: Ennominae) - Matson, Tanner A. (Zootaxa, 2022)
The monotypic Metrica new genus is described for Metrica kuschea (Guedet, 1939) new combination. The genus is placed in the tribe Ennomini Duponchel and hypothesized to be most closely related to a Neotropical species of “Isochromodes” Warren. Adult morphology, including male and female genitalia are illustrated, and molecular data supporting the transfer of “Semiothisa” kuschea (Macariini Guenée) to the Ennomini are presented.